PelatihanIncredible Teacher Untuk Meningkatkan Kompetensi Guru Di Sekolah Dasar Inklusi Banda Aceh - Safira, Ayu, Dr. Lisnawati Ruhaena, M.Si, Juliani Prasetyaningrum, M.Si (2016)
The experimental research attemped to describe the effect of incredible teacher's training in improving the teacher's competencies at Inclusive elementary school. The subjects of this research are 22 teachers who are teaching in Inclusive elementary school at Banda Aceh. The subjects are divided into two groups. The first group consists of 11 teachers that joint the training. In the other hand, the second group consists of 11 teachers that do not join the training. The method that used by the writer in this research is pretest - posttest control group design. This research takes time for three days. The lesson during the training incredible teacher are understanding special need children, identify special need children, the effective communication, therapy that used for special need children, learning programs for special need children and role play. The collected data is used by writer is the teacher's competency scale through pretest, post test and follow up. The result of analyses data of pretest, post test and follow up by using fried men test show chi-square=19.400 with the significant score 0.000 (P<0,05). So, we can conclude that incredible teacher's training can improve the teacher's competencies effectively and significant.